DEVELOPMENT OF AUGMENTED REALITY (AR) LEARNING MEDIA ON DIGESTIVE SYSTEM MATERIALS IN IMPROVING THE UNDERSTANDING OF CONCEPTS FOR STUDENTS OF CLASS XI MAN 2 LANGKAT: PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) PADA MATERI SISTEM PENCERNAAN DALAM ‎MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK ‎KELAS XI MAN 2 LANGKAT - Helpi Tiana; Rohani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study is a type of research and Development (R&D) which aims to develop augmented ‎Reality (AR) based learning media on the topic of the human digestive system for high school ‎students. This study was initiated because of the increasing need for interactive learning media that ‎are able to visualize abstract biological concepts and support * independent curriculum*, which ‎emphasizes meaningful and technology-oriented learning. The development process follows the 4-‎D model (Define, Design, Develop, Disseminate) introduced by Thiagarajan, but this study was ‎limited to the Develop stage due to time constraints. Research instruments include expert ‎validation sheets, teacher and student practicalities questionnaires, and pretest and posttest ‎assessments to measure media effectiveness. The validation results of 98% media experts and 88% ‎material experts showed that the media is very feasible. The practical test received a score of 90% ‎from teachers and 98% from students, both belonging to the “very practical”category. Furthermore, ‎the effectiveness test showed an increase in students ' conceptual understanding, with an average ‎N-Gain score of 76.52%, which is high. These results indicate that AR-based learning media are ‎effective in increasing students ' engagement and conceptual understanding of the human digestive ‎system.